To convict an innocent or to let a guilty person go free: preference for false positive outcomes of criminal trials in a nationwide representative sample for Germany = Einen Unschuldigen verurteilen oder einen Schuldigen auf freien Fuß setzen: Präferenz für falsch positive Ergebnisse von Strafverfahren in einer bundesweit repräsentativen Stichprobe für Deutschland - Uhl, Andrzej (Kriminologie - das Online-Journal, 2023)
Although it is broadly agreed within jurisprudence that wrongful convictions should be avoided even at the cost of effective prosecution, such a view has been losing popularity globally with the general public, who increasingly prioritisethe punishment of the guilty over the non-punishment of the innocent.This study attempts to extend the limited research into public opinion on the trade-off between wrongful convictions and erroneous acquittals. A representative sample ofGerman ISSP (German edition of In-ternational Social Survey Program) respondents is employed to test a set of hypotheses regarding pref-erence for either error of justice. The aversion to punishment of an innocent person was particularly strong among west German respondents and respondents with high educational attainment, while no distinct preference was established for social groups marked by a high fear of crime or at risk of wrongful conviction. At odds with codified rules on evidence and procedural safeguards, legalists, who advocate unconditional adherence to the law, would often rather see the innocent condemned than the guilty acquitted. These findings are subsequently compared with studies conducted in other jurisdictions and discussed in consideration of the social and cultural norms of contemporary German society. The results can fill a research gap by explaining aspects that shape the readiness to sacrifice the freedom of a poten-tially criminal other to protect the remainder of society against perceived threats.